Asymmetrical Microchannel Emulsification Plates for Production of Small‐Sized Monodispersed Emulsion Droplets. Issue 12 (29th August 2017) - Khalid, Nauman; Kobayashi, Isao; Uemura, Kunihiko; Nakajima, Mitsutoshi
Abstract: Monodispersed emulsion droplets have promising advantages in food, pharmaceutical, and chemical industries. Previous microchannel emulsification (MCE) plates having the capacity of generating small‐sized droplets exhibited very low droplet productivity since these plates operate at a low dispersed‐phase flow rate and with a relatively small number of microchannels. An innovative MCE plate with 176 176 circular asymmetric through‐holes was manufactured, which is comprised of a series of discrete outlets on each microchannel line with an effective cross‐sectional area of 1 cm 2 . The newly fabricated MCE plate is capable to produce monodispersed emulsion droplets with small Sauter mean diameters. Abstract : Microchannel emulsification is a progressive technique for production of monodispersed emulsion droplets with great potential in food, pharmaceutical, and chemical industries. An asymmetrical straight‐through microchannel emulsification plate for generation of small uniform droplets with higher productivity was designed, intended for mass production of monodispersed small‐sized droplets.